Factors affecting the consumer awareness towards halal products in Kuala Krai / Wan Nurhayati Wan Hasan - Wan Hasan, Wan Nurhayati (Bachelor of Science (Hons.) Statistics, 2015)
The researcher aims to investigate the factors that affect the consumer awareness towards halal products in Kuala Krai, Kelantan. 220 respondents were involved in this study was selected by using simple random sampling. The relationships among the variables were analysed using Structural Equation Modelling (SEM) approach, independent sample t-test and Analysis of Variance (ANOVA). By using SEM, the researcher also able to asses and modify the measurement model as well as the structural model. From the analysis of structural model showed that there was significant relationship between religion belief and marketing concept with consumer awareness towards halal products. In addition, the independent sample t-test and Analysis of Variance (ANOVA), it showed that there was no significance difference of the gender, age, marital status, level of education, occupation and monthly income on consumer awareness towards halal products. Only race showed a significant difference on consumer awareness towards halal products